The feasibility and acceptability of clean fuel use among rural households. A pilot study in Central Ghana - Theresa Tawiah; Seidu Iddrisu; Stephanie Gyaase; Mieks Twumasi; Kwaku Poku Asante; Darby Jack (AOSIS, 2022)
Background: 76% of the population in Ghana uses solid fuels as their primary source of cooking energy, including 41.3% firewood and 31.5% charcoal. Consequently, household air pollution (HAP) continues to be the leading risk factor for the majority of illness burden in the country. In the past, aggressive LPG distribution and adoption schemes have been implemented to reduce HAP in Ghana. Nevertheless, just 22% of Ghanaian households utilize LPG for cooking. Aims:  The purpose of this study was to determine the viability and acceptability of four clean fuels among rural households in central Ghana, both separately and in combination. Methods:  Quantitative and qualitative methods were used to conduct this study. The Kintampo Health Demographic Surveillance System was used to randomly pick ten homes who exclusively utilized biomass fuel. For each family (n = 10), we gave four stove and fuel combinations that were both clean. The stoves were utilized for two weeks, and free fuel was supplied. After each two-week trial period, interviews were conducted to gauge stove acceptance, with an emphasis on finding the specific energy requirements that each stove satisfied. Conclusions:  LPG and ethanol stoves were the most popular among rural families, according to our data. In comparison to Mimi Moto and electric induction stoves, the two stoves were favoured because they were easier to use and clean, cooked faster, were deemed safer, and enabled a variety of cooking styles. Participants' stove preferences appear to be primarily influenced by two domains: 1) realizing the benefits of clean stove technology and 2) overcoming early anxiety of clean stove use, particularly LPG.